Animal Welfare Compromises Associated with Causes of Death in Neonatal Piglets - Kirsty L. Chidgey; Nutnapong Udomteerasuwat; Patrick C. H. Morel; Fernanda Castillo-Alcala (Animals, 2022)
This pilot study aimed to assess the welfare impacts of different causes of pre-weaning deaths in piglets. Piglets that died between 0–7 days after birth (n = 106) were collected from two commercial pig farms and subject to post-mortem examination to confirm their cause of death as well as any contributing factors. Using the Five Domains Model, the most likely affective experiences associated with the pathological findings were carefully inferred to better understand affective experience as it related to known causes of liveborn piglet mortality. The most common causes of liveborn piglet mortality were starvation (23%), crushing (23%) and non-viable (21%). Thirty one piglets had evidence of starvation, but it was only considered the primary cause of death in 15 piglets, as cofactors such as poor viability (n = 13) were also present in many piglets with evidence of starvation. All 15 piglets that were crushed died within 24 h after birth and most had evidence of thoracic and/or abdominal internal bleeding. This study found that common causes of liveborn piglet death were associated with compromises in Domains 1 (Nutrition/hydration), 3 (Health/function), and4 (Behavioural interactions), with the most likely resulting affective states described in Domain 5 (Mental state). This highlights the interaction between physical/functional and situation-related (behavioural) aspects that influence an animals’ welfare status.